Promiscuity in Lichens Follows Clear Rules: Partner Switching in Cladonia Is Regulated by Climatic Factors and Soil Chemistry - Škvorová, Zuzana; Černajová, Ivana; Steinová, Jana; Peksa, Ondřej; Moya, Patricia; Škaloud, Pavel (Frontiers in Microbiology, 2022)
Climatic factors, soil chemistry and geography are considered as major factors affecting lichen distribution and diversity. To determine how these factors limit or support the associations between the symbiotic partners, we revise the lichen symbiosis as a network of relationships here. More than one thousand thalli of terricolous Cladonia lichens were collected at sites with a wide range of soil chemical properties from seven biogeographical regions of Europe. A total of 18 OTUs of the algal genus Asterochloris and 181 OTUs of Cladonia mycobiont were identified. We displayed all realized pairwise mycobiont–photobiont relationships and performed modularity analysis. It revealed four virtually separated modules of cooperating OTUs. The modules differed in mean annual temperature, isothermality, precipitation, evapotranspiration, soil pH, nitrogen, and carbon contents. Photobiont switching was strictly limited to algae from one module, i.e., algae of similar ecological preferences, and only few mycobionts were able to cooperate with photobionts from different modules. Thus, Cladonia mycobionts generally cannot widen their ecological niches through photobiont switching. The modules also differed in the functional traits of the mycobionts, e.g., sexual reproduction rate, presence of soredia, and thallus type. These traits may represent adaptations to the environmental conditions that drive the differentiation of the modules. In conclusion, the promiscuity in Cladonia mycobionts is strictly limited by climatic factors and soil chemistry.